2019
DOI: 10.1002/btpr.2863
|View full text |Cite
|
Sign up to set email alerts
|

Efficient succinic acid production from high‐sugar‐content beverages by Actinobacillus succinogenes

Abstract: This study presents the production of succinic acid (SA) by Actinobacillus succinogenes using high‐sugar‐content beverages (HSCBs) as feedstock. The aim of this study was the valorization of a by‐product stream from the beverage industry for the production of an important building block chemical, such as SA. Three types of commercial beverages were investigated: fruit juices (pineapple and ace), syrups (almond), and soft drinks (cola and lemon). They contained mainly glucose, fructose, and sucrose at high conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…The author of [30] reported that the succinic acid production stopped when the concentration of the microbially produced acid mixture reached a value of 45 g L −1 . With values of 49 g L −1 (A. succinogenes) and 44 g L −1 (B. succiniciproducens) found in the present study, the fermentation of medium C Y resulted in concentrations in a similar range as that described by [31]. Therefore, the lowered yield might have occurred due to product inhibition.…”
Section: Optimizing the Sugar Concentration For A Succinogenes And B Succiniciproducenssupporting
confidence: 72%
“…The author of [30] reported that the succinic acid production stopped when the concentration of the microbially produced acid mixture reached a value of 45 g L −1 . With values of 49 g L −1 (A. succinogenes) and 44 g L −1 (B. succiniciproducens) found in the present study, the fermentation of medium C Y resulted in concentrations in a similar range as that described by [31]. Therefore, the lowered yield might have occurred due to product inhibition.…”
Section: Optimizing the Sugar Concentration For A Succinogenes And B Succiniciproducenssupporting
confidence: 72%
“…The residual sugar concentrations were 16 The results indicate a lack of protein or other essential nutrients, such as vitamins, that are contained in yeast extract. [32] determined a sugar consumption of only 65 % during the fermentation of diluted pineapple juice showing an initial sugar concentration of 56 g L -1 . [32] were able to increase the sugar consumption to 82 % due to the supplementation with 5 g L -1 yeast extract and minerals.…”
Section: Yeast Supplementation For Optimization Of Succinic Acid Fermentationmentioning
confidence: 99%
“…[32] determined a sugar consumption of only 65 % during the fermentation of diluted pineapple juice showing an initial sugar concentration of 56 g L -1 . [32] were able to increase the sugar consumption to 82 % due to the supplementation with 5 g L -1 yeast extract and minerals. The resulting initial sugar to yeast extract ratio of 11 was even higher than the optimal ratio of 5.8 derived from the model verification of [24].…”
Section: Yeast Supplementation For Optimization Of Succinic Acid Fermentationmentioning
confidence: 99%
“…Succinic acid's importance is highlighted by its projected 2025 annual market size of over 115000 tons (MarketWatch 2019). This projected high market share is due to the capacity of succinic acid to be employed in a variety of high-value specialized applications such as in of the pharmaceutical and food industry and large volume applications in the chemical industry for the production of plasticizers, polyurethanes, and useful chemical intermediates (Ferone et al 2019). Interestingly, despite the notable opportunity to produce succinic acid as a high-value platform chemical from waste apple slurry, at the time of preparing this manuscript, only one study by González-García et al (2018) reported life cycle assessment of the waste apple slurry for bio-succinic acid production.…”
Section: Introductionmentioning
confidence: 99%